Correlates of frailty phenotype and frailty index and their associations with clinical outcomes. Issue 10 (24th July 2017) - Guaraldi, G; Malagoli, A; Theou, O; Brothers, TD; Wallace, LMK; Torelli, R; Mussini, C; Sartini, S; Kirkland, SA; Rockwood, K
Abstract : Objectives: Frailty is a predictor of adverse health outcomes and can be measured across the life course, including among people living with HIV. The purpose of this study was to examine two commonly used measures of frailty ‐ the frailty index (FI) and frailty phenotype – to assess common characteristics and to describe associations with multimorbidity, falls, and disability in people aging with HIV. Methods: This was a cross‐sectional observational study including 482 consecutive HIV‐infected patients (mean age 53.9 ± SD 6.9 years; 75% male) attending the multidisciplinary metabolic clinic at the University of Modena, Italy. Frailty was measured with the frailty phenotype and a 37‐item FI. Results: The mean FI score was 0.28±0.1 and frailty phenotype categories were: 3.1% frail, 51.9% pre‐frail, and 45% robust. The duration of antiretroviral therapy was significantly different across levels of frailty as measured by both frailty tools ( P < 0.01), but the nadir CD4 count was only significant for the FI ( P = 0.01); current CD4 count was not significantly different across frailty levels using either tool. Both frailty measures were associated with multimorbidity; the FI was associated with Instrumental Activities of Daily Living impairment and falls history, whereas the frailty phenotype was not. Conclusions: The frailty phenotype and the FI demonstrated similar characteristics in patients at a tertiary‐level HIV clinic. The FI had a stronger association with age, nadir CD4 count, comorbidities, falls, and disability. Integrating frailty assessments in clinical practice will be crucial for the development of interventions in age‐related conditions, including disability and falls, in older persons living with HIV.